Violence suffered by young women as a result of their partner's alcohol consumption - Acevedo López, María Nallely (2022)
Objective: To understand the violence suffered by young adults as a result of their partner's alcohol consumption. Method: Qualitative, descriptive study. It was conducted from September 2021 to May 2022. The selection of participants was by purposive sampling, with a total of seven participants per availability. Data collection through semi-structured interview; participants gave their informed consent and the thematic analysis was performed. Main results: After the analysis, 6 themes were constructed: alcohol and couple relationship, types of violence, jealousy and machismo, perception of increased alcohol consumption by the partner, mixed emotions during the relationship, and support networks. General conclusion: The study participants discovered how the relationship with their partner changed as a consequence of alcohol consumption, articulated with attitudes of machismo and among the most common violence received included physical, psychological, sexual, economic and family damage.